Effect of rare earth content on TbF3 diffusion in sintered Nd–Fe–B magnets by electrophoretic deposition. (1st April 2017) - Cao, Xuejing; Chen, Ling; Guo, Shuai; Fan, Fengchun; Chen, Renjie; Yan, Aru
Abstract: The impact of starting magnets with different rare earth (RE) content on the coercivity and microstructural properties of TbF3 diffused sintered Nd–Fe–B magnets using electrophoretic deposition (EPD) method was investigated. In the diffused samples with the RE content of 30 wt.%, the coercivity achieved the largest enhancement and the increment was 801 kA/m with less than 0.81 wt.% Tb. Microstructure analysis suggested that higher RE content was helpful to the Tb diffusion process and further contributed to the higher coercivity. Mechanism of coercivity enhancement and Tb diffusion was discussed based on the observation. Graphical abstract: